Terrorism and its impact on taxation and national development in Nigeria - Agbonika, Josephine A. A. (African journal of law and criminology, 2015)
This paper traces the history of terrorism in Nigeria and evaluate its effects on national development and religion. It also shows the crisis from other nations where such disturbances have existed and provides lessons to be learnt by Nigeria. No nation can afford to treat with levity the security of its territorial integrity and of its people. Indeed every aspect of human endeavor, such as health, environmental, agricultural, economic, political, social and physiological, stand to be greatly affected by the state of security or insecurity of any nation. In the face of the Boko Haram uprising, Nigeria has been thrown into confusion about how to handle its security issues. The call on the international community for assistance does not seem to have yielded positive results since the faceless group continues to use suicide bombers to attack intermittently.